Dynamics of pneumatic and hydraulic transport technological equipment - Bogdevičius, Marijonas; Matuliauskas, Arvydas; Mištinas, Vygantas; Spruogis, Bronislovas; Suslavičius, Vladimiras (Transport, 2004)
In the article the classification of inpipe robots is presented, their advantages and imperfections are reviewed. The schemes of the construction of the wall press walking inpipe robot with a pneumatic drive and an inpipe robot with a vibratory pneumatic drive are given. The analysis of the identification method of leaks occurring due to damages of the linear part of the main oil pipelines is carried out. The momentum and continuity equations of viscous compressible fluid in a pressure pipeline are presented. Differential equations of fluid movement in the oil pipeline are solved by the method of characteristics. Variation diagrams of pressure and velocity of fluid in a leaking oil pipeline are presented. The impulsive extinguishing systems are presented.First Published Online: 27 Oct 2010